Model for digital healthcare ecosystem based on blockchain technology: a pilot study - Bjelica, Artur; Bjelica, Daniel; Despotović-Zrakić, Marijana; Labus, Aleksandra (E-business technologies conference proceedings, 2021)
The aim of this study is to identify crucial factors that influence the acceptance of a digital healthcare ecosystem based on blockchain technology. Theoretical framework for the proposed model relies on the theory of stakeholders, TAM theory, and concept of readiness for changes. Statistical analysis was performed on the basis of Structural Equation Modeling (SEM). The proposed model may facilitate the use adoption of the healthcare ecosystem based on blockchain technology.